2010
DOI: 10.1016/j.jphysparis.2009.11.010
|View full text |Cite
|
Sign up to set email alerts
|

A model of neural mechanisms in monocular transparent motion perception

Abstract: Transparent motion is perceived when multiple motions are presented in the same part of visual space which moves in different directions. Several psychophysical as well as physiological experiments have studied the conditions under which motion transparency occurs. Few model mechanisms have been proposed to segregate multiple motions. We present a novel neural model which investigates the necessary mechanisms underlying initial motion detection, the required representations for velocity coding, and the integra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

6
1

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 47 publications
(48 reference statements)
1
19
0
Order By: Relevance
“…We have demonstrated that such separate but temporally overlapping phases can be accounted for by a recurrent network of mutually interacting neuronal sites. The network model has been composed of the same components like the present model architecture (Raudies and Neumann, 2010). It would thus be interesting to reveal whether similar temporal phases can be identified for model V4 cells that may give rise to identify different signatures indicative of contributions from delayed neuronal mechanisms that are involved in the computation of figural shape information.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have demonstrated that such separate but temporally overlapping phases can be accounted for by a recurrent network of mutually interacting neuronal sites. The network model has been composed of the same components like the present model architecture (Raudies and Neumann, 2010). It would thus be interesting to reveal whether similar temporal phases can be identified for model V4 cells that may give rise to identify different signatures indicative of contributions from delayed neuronal mechanisms that are involved in the computation of figural shape information.…”
Section: Discussionmentioning
confidence: 99%
“…This model architecture has previously been used in various approaches touching different domains, such as the disambiguation of local motion (Bayerl and Neumann, 2004; Beck and Neumann, 2011), the processing of transparent motion (Raudies and Neumann, 2010) the detection of texture boundaries (Thielscher and Neumann, 2003), the extraction of object boundaries using texture compression (Weidenbacher and Neumann, 2009), and the analysis and representation of biological motion sequences (Layher et al, 2014). …”
Section: Model Definitionmentioning
confidence: 99%
“…Transparent and semitransparent motion occurs whenever multiple motions are presented in the same part of visual space moving in different directions or with different speeds. The model of Raudies and Neumann [17] investigates the necessary mechanisms underlying initial motion detection, the required representations for velocity coding, and the integration and segregation of motion stimuli to account for the perception of transparent motion.…”
Section: Further Extensions Of the Model Frameworkmentioning
confidence: 99%
“…Despite its simplicity, the model is able to explain experimental data and, without parameter changes, to successfully process realworld data used for model benchmarking [12,13]. In all, the paper summarizes some previous work of the authors, namely, work of [14][15][16][17] by using a common framework of model description. Most importantly, the framework has been extended such that different neural interaction schemes can be utilized in different variants of the model.…”
Section: Introductionmentioning
confidence: 99%
“…In the second step of the three-stage processing cascade, FB from other model areas or an attention signal (Raudies & Neumann, 2010) could be included in principle. However, in the current model, areas V2 or MT are the highest areas in the model and do not receive any modulating input, nor do they incorporate any attention signal.…”
mentioning
confidence: 99%